1999
DOI: 10.1034/j.1600-0501.1999.100102.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate functional loading of Brånemark dental implants. An l8‐month clinical follow‐up study

Abstract: A clinical and radiographical study was performed to compare the outcome of oral rehabilitation in the edentulous mandible by fixed supraconstructions connected to implants installed according to either i) a 1-stage surgical procedure and immediate loading (Experimental Group-EG), or ii) the original 2-stage concept (Reference Group-RG). The EG comprised 16 subjects with edentulous mandibles. Beyond the non-smoking criteria the following specific inclusion criteria were adopted: i) all patients had to consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
201
2
14

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(232 citation statements)
references
References 0 publications
9
201
2
14
Order By: Relevance
“…3,4 There are several options for treating a mandibular edentulous patient, all of which have high published survival rates, such as implant overdentures (immediate or delayed loading), implant fixed complete dental prostheses (immediate or delayed loading), and others. Randow et al 19 compared immediate loading with the original delayed loading concept. During the 18-month observation period, no implant was lost in either of the two groups, and the authors concluded that the immediate-loading treatment had high implant survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 There are several options for treating a mandibular edentulous patient, all of which have high published survival rates, such as implant overdentures (immediate or delayed loading), implant fixed complete dental prostheses (immediate or delayed loading), and others. Randow et al 19 compared immediate loading with the original delayed loading concept. During the 18-month observation period, no implant was lost in either of the two groups, and the authors concluded that the immediate-loading treatment had high implant survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Randow y cols. 34 compararon la rehabilitación de maxilares inferiores desdentados con prótesis implantosoportadas fijas usando dos protocolos, uno de carga inmediata y otro en dos fases, de carga diferida. En este segundo grupo, los pacientes no usaron prótesis durante 10 días.…”
Section: Followed the Progress Of 69 Immediately Loaded Implants And unclassified
“…The surface was covered with collagen membrane and secured with interrupted sutures. The ball abutments were screwed to the implant body as adequate primary stability for immediate loading of implants was achieved [4,5].…”
Section: Techniquementioning
confidence: 99%